EVALUASI KINERJA WILAYATUL HISBAH DALAM PENERAPAN SYARI’AT ISLAM DI KOTA LHOKSEUMAWE - Nazaruddin Nazaruddin; Ahmad Yani; Ti Aisyah; Suci Fitri Annisa (Al-Madaris Jurnal Pendidikan dan Studi Keislaman, 2021)
Performance evaluation is an activity carried out by management to assess the performance of employees in an institution or organization by comparing predetermined job descriptions. Ikhtilath is an act of making love between a man and a woman who is not a mahram in the open. Which has been regulated in Aceh Qanun Number 6 of 2014. However, realizing Islamic Shari'at in Lhokseumawe City still has problems, especially in the application of Islamic Shari'at regarding Iktilath violations. It is proven by the occurrence of Ikhtilath's actions in open places and the lack of supervision and socialization of Wilayatul Hisbah has not been maximized, so that many people do not care about the rules in Islamic Shari'at, this shows that violations of Ikhtilat still occur in Lhokseumawe City. The results of the study show that the performance of Wilayatul Hisbah in the application of Islamic Sharia has not been running optimally. This is evidenced by the increase in Qanun violations every year and people who do not fully know the rules of Islamic Shari'at as a whole due to the lack of socialization and supervision carried out by Wilayatul Hisbah as a party who to be responsible. It is hoped that the Islamic Sharia Institution will be able to monitor and socialize the Islamic Shari'at maximally, especially in the implementation of Ikhtilath violations. As well as the existence of cooperation between the government and the community so that the implementation of Islamic Shari'ah can run in a kaffah manner.